Modern houses of the world - Cantacuzino, Sherban (New York : Dutton Vist, 1965)
Ejemplos de obras de arquitectos reconocidos mundialmente: <Wright, Frank Lloyd>; <Jhonson, Philip>; <Rudolph, Paul>; <Rietveld, Gerrit Thomas>; <Jacobsen, Arne>; <Le Corbusier>; <Niemeyer, Oscar>; <Gropius, Walter>; <Saarinen, Eero>.
Keywords: VIVIENDAS UNIFAMILIARES; VIVIENDAS RESIDENCIALES; SIGLO XX